Acoustic Velocity Correcting Method for the Tilted Acoustic Tube in Testing of Pile by Ultrasonic Transmission - Yongqiang Cui; Zhitao Ma; Yachao Yang; Daifu Song (Advances in Civil Engineering)
The finite element software ABAQUS was used to simulate the detection of piles by ultrasonic transmission. The influence of the tilted acoustic tube on the testing results of the pile was analyzed. The results showed that, when the pile was complete, the velocity of the sound-depth curve of the received signal was inclined to one side due to the inclination of the acoustic tube and the velocity of the sound seriously deviated from the normal value; when there was a defect in the pile, the signal of the defect was not obvious due to the tilt of the acoustic tube, which was easy to miss or misjudge the defects of the pile. To solve the problem of the inclined acoustic tube, the mathematical model of the position relation of the acoustic tube was established, and the method for correcting the velocity of the sound based on the angle of the acoustic tube was derived. Numerical simulation and engineering examples were used to verify the modified method; the verification showed that the corrected acoustic signal could accurately determine the defects and their positions in the pile, and this method effectively reduced the influence of the tilted acoustic tube on the detection signal, which was beneficial to improve the accuracy of the testing for the pile.